2005
DOI: 10.1080/02102412.2005.10779561
|View full text |Cite
|
Sign up to set email alerts
|

La experiencia y el comportamiento ético de los Auditores: un Estudio Empírico

Abstract: RESUMEN El desarrollo de la profesión de auditoría conlleva situaciones en las que el auditor se enfrenta a dilemas de carácter ético. Su comportamiento para obtener una solución a los mismos requiere la utilización de un proceso de toma de decisiones donde adquieren especial importancia los valores éticos individuales. En un estudio anterior abordamos el análisis de la ponderación que los auditores españoles establecen de determinados factores que son considerados predictores de comportamiento ético. Asimismo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Lin and Zhang (2011) show, in analyses of the ethical sensitivity of accountants, that as the work experience of the subjects studied increases, so does their standard of ethical behavior. Also Sierra Molina and Orta Pérez (2005) found a positive relationship between auditors experience and ethical values. By contrast, other studies on auditors and financial managers have concluded that experience (Ponemon, 1992) has a significant but negative impact on the level of ethical reasoning and also that older auditors showed lower levels of moral reasoning than younger ones (Eynon et al, 1997).…”
Section: Ethical Judgment Of Questionable Practicesmentioning
confidence: 95%
“…Lin and Zhang (2011) show, in analyses of the ethical sensitivity of accountants, that as the work experience of the subjects studied increases, so does their standard of ethical behavior. Also Sierra Molina and Orta Pérez (2005) found a positive relationship between auditors experience and ethical values. By contrast, other studies on auditors and financial managers have concluded that experience (Ponemon, 1992) has a significant but negative impact on the level of ethical reasoning and also that older auditors showed lower levels of moral reasoning than younger ones (Eynon et al, 1997).…”
Section: Ethical Judgment Of Questionable Practicesmentioning
confidence: 95%
“…A level of 5 percent was used as the criterion for identifying significant differences. This statistical test has been successfully used in other studies on accounting and auditing carried out in Spain and other countries using questionnaire-based surveys (García Benau et al, 2000;Duréndez Gómez-Guillamón, 2003;Sierra Molina and Orta Pérez, 2005;Beattie et al, 2006;Al-khabash and Al-Thuneibat, 2009). As other studies have done, non-parametric Mann-Whitney tests were also used to corroborate the results (see, for instance, Fuentes Barberá and Pucheta Martínez, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…This study contributes a conscientious effort to adapt the MES, including its items and scenarios, to the Latin-American cultural context, pointed out as necessary by many researchers over many years [e.g., 13,63]. Furthermore, the scenarios' selection followed the specific and rigorous approach offered by Mudrack and Mason [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the criticism of different MES versions, the MES-30 was adapted to the Spanish language, according to the following reasons: (a) although some research have reported translations of different MES versions [e.g., 13,28,46,63], none of them aimed at actually adapting the instrument; (b) the MES-8 does not contain items from the utilitarianism and egoism philosophical approaches, which provide relevant criteria for ethical judgment; and (c) both MES-8 and MES-12 contain philosophical approaches evaluated by a very little number of items. Only the MES-30 follows the recommendation that there should be at least three items per factor [50].…”
Section: Spanish Adaptation Of the Mes-30mentioning
confidence: 99%